Attack and serve performances according to the match period and quality of opposition in elite volleyball matches - Marcelino, R. O.; Sampaio, J. E.; Mesquita, I. M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine attack and serve performances in the beginning and end of the initial and final sets of volleyball matches according to the quality of opposition. Six hundred rallies from the Men's World Cup 2007 were selectively sampled from a total of 5,117 rallies observed using video match analysis. Rally-by-rally double moving averages of serve and attack efficacy were plotted by 4 different match periods (first 15 rallies of the initial set; first 15 rallies of the final set; last 15 rallies of the initial set; and last 15 rallies of the final set). Approximate entropy values were calculated to analyze the amount of data randomness. The results were examined according to the quality of opposition in 2 types of games: higher level (HIGH) including the first 4 ranked teams and lower level (LOW) composed of the last 5 ranked teams. The results suggested that volleyball matches presented different profiles depending on the match period. Considering the teams' level, a greater adaptation was found within the HIGH × HIGH matches according to the match period and a more strategic use of the serve and attack tactics taking into account the type of the set (initial or final set) and the period (beginning or end of the set). The findings emphasize the need for coaches and players to perceive the most important points at the end of the set and to manage their effort throughout the match attempting to reach this period in optimal condition. Therefore, it might be beneficial to coaches to stress the need to perform at the highest level, particularly at the end of the training drills that simulate competition scenarios.